Measuring the impact of promotional activity - Wheeler, Martin (Henry Stewart Talks, 2010)
The promotional landscape is changing, Measuring volumetric impact, What drives incremental sales?, Volume is correlated to price, Promotional dynamics, Discount and display, The true picture of incremental volume, Measuring the commercial impact of promotional activity, Key metrics, Share analysis, Effectiveness vs. efficiency, Using insight to develop promotional strategy, Funding and negotiation